Z-numbers Based Hybrid MCDM Approach for Energy Resources Ranking and Selection - Nuriyev, Mahammad (International Journal of Energy Economics and Policy, 2020)
Energy resource selection is a multi-criteria decision-making task, and in most cases, it is characterized by uncertainties, information incompleteness, and vagueness. In such circumstances, a group decision making and experts` opinion study are appropriate approaches for the problem solution. These approaches allow to a considerable extent to compensate the deficiency of the relevant and reliable data on alternatives and decision-makers’ priorities. In this paper fuzzy information and Z-numbers based MCDM models have been studied and used as a group decision-making tool for energy resources ranking and selection. In order to make a well-founded and reliable decision and to get insights how methodological backgrounds of models used are influencing results of evaluations, comparative study of applications of the outranking, distance-based and pairwise comparisons methods for the same subject area is carried out and merits and demerits of each approach from a decision-makers’ point of view are evaluated. The availability of solutions based on various approaches allows to decision-maker to select the more justified and consistent solution. A numerical example of energy resources ranking and selection for Azerbaijan illustrates the efficiency of the integrated approach and comparative study. Keywords: multi-criteria decision, fuzzy, Z-number, energy resources. JEL Classifications: D81, P48, Q35, Q42 DOI: https://doi.org/10.32479/ijeep.9950